Taska Mall (Service) - Sidi, Richie; Masuning, Mc'O Bryant; Halid, Armila Ashyikin; Maidi, Diniy Ammarah; Gani, Nazira; ., Siti Nur Shakinah (2014)
D'azka company is the business about care the babies and the business will start on the end of 2014. This service will provide to all parent especially for those like to shopping and worries to bring their children during shop. This business are located at second floor One Borneo Hypermall, Kota Kinabalu. This location are strategic because this the only one mall are familar at that area and far away from others mall. This will give a good potential especially for our new business. This business is to prevent the number of missing children in the mall. This cases always happened because the negligent of their own parents. After made some research, we decided to begin our company at One Borneo Hypermall. Kota Kinabalu because that more secure for start our business. During the promotion, our company will tell all about company policies and make customer believe that we as a legal company. This to avoid some confuse among customer about our service. We believe that our business has potential to compete with other nursery because in this area no more nursery except playground. Besides that, the numbers of customer visit to this mall are satisfied because most of them live nearby the mall and make them want to shop in the One Borneo Hypermall only.